Automatic management technology of object storage systems - Doudou HU; Fei LUO; Yuan ZHANG (Dianxin kexue)
The object storage system not only breaks the bottleneck of the traditional SAN storage system,but also achieves the expansion of performance and capacity linearly in video monitoring field.However,the remote management for the resources of the object storage system has become a problem for managers.Aiming at this problem,the method and related technology of automatic management of object storage cluster was studied,so as to improve the efficiency of storage cluster.The functions of the automatic management system included remote lauching,stopping and resetting of cluster components,monitoring of running status,cluster expansion and log viewing and storage.Based on Ceph object storage cluster,the automated management system for Web application service platform was achieved,monitoring and management was realized effectively ultimately,and the nodes of the cluster and the storage capacity were expanded automatically.